(NpROIZWEDENIQ(B: [1907-1914] /s (N~ASTX (B3s - (NbUNIN(B, (NiWAN aLEKSEEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1987)
(Nw TRETIJ TOM sOBRANIQ sO^INENIJ i(B. (Na(B. (NbUNINA PO[LI POWESTI (B"(NdEREWNQ(B" (NI (B"(NsUHODOL(B", (NRASSKAZY (B1909 - 1914 (NGODOW I CIKL (B"(NpUTEWYH PO\M(B", (NOB_EDINENNYH POD NAZWANIEM (B"(NtENX pTICY(B"s
rus
Keywords: (NpOWESTI I RASSKAZYs